Estrategias didácticas para corregir la disortografía en el proceso enseñanza-aprendizaje en el área de lengua y literatura de los niños y niñas del segundo grado paralelo a del subnivel básica elemental, de la escuela de educación básica Gabriela Mistral nº1 del cantón Catamayo, provincia de Loja, Período lectivo 2013-2014 - Torres Romero, Tatiana Marivel (2015)
This thesis titled: TEACHING STRATEGIES TO CORRECT THE dysorthography IN LEARNING PROCESS IN THE AREA OF LANGUAGE AND LITERATURE FOR CHILDREN OF SECOND DEGREE PARALLEL TO THE BASIC sublevel ELEMENTARY SCHOOL GABRIELA MISTRAL No.1 BASIC EDUCATION OF CANTON CATAMAYO, province of Loja, LECTIVO PERIOD 2013-2014, had as general objective: to determine the teaching strategies to correct dysorthography in the teaching-learning process by teachers of children of the second parallel Grade A Basic sublevel Elemental, School of Basic Education Gabriela Mistral # 1 of Catamayo Canton province of Loja, school 2013-2014. To carry out the research work the following methods were used: descriptive analytic and synthetic; and as art: the survey, it was applied to teaching and students of the institution, the sample consisted of 27 students and a teacher, for the analysis and interpretation of data statistical tables and graphic representation was used. After processing the information stated in conclusion that the teacher does not apply strategies to improve dysorthography, reality is captured because the diagnostic results found that 52% of students did not differentiate phonemes, sounds, word formation and prayers, if you have data that difference after applying the workshops where a total of 80% reaffirmed this knowledge; after discussing these results is set to conclude that the methods worked during the workshop are significant because it allowed enhance learning, for which the teacher is advised to apply the format appropriate spaces workshops with students.